Karimah Ashadu - tendered / edited by Bianca Stoppani with Alessandro Rabbotini and Leonardo Bigazzi. - Stoppani, Bianca; Rabottini, Alessandro; Bigazzi, Leonardo; Ashadu, Karimah (Mousse Publishing, 2025)
Published on the occasion of Ashadu's first institutional exhibitions in London at Camden Art Centre, and Chicago at the Renaissance Society, this detailed overview of her filmic practice features newly commissioned essays, an extended conversation with the artist and a collection of synopses documenting her video installations. It is a rich resource for readers who hope to gain an understanding of the breadth of Ashadu's work to date, which engages with contemporary manifestations of Nigerian history borne by its people and landscapes.